2011
DOI: 10.1144/sp354.7
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoshorelines of glacial Lake Kuray–Chuja, south-central Siberia: form, sediments and process

Abstract: Glacial lake Kuray-Chuja which occupied the Kuray and Chuja Basins during the Quaternary Period (Marine Isotope Stages 2 and 3) left distinct shoreline features around the basin margins. At the greatest extent the lake had a surface area of 2951 km 2 with wind fetches up to 70 km. Wind waves constructed erosional, erosional-accumulative and accumulative strandlines, the latter including spits, tombolos, barrier beaches and offshore bars. Strandlines range in altitude between c. 1600 and 2100 m, the range in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
0
16
1
1
Order By: Relevance
“…Similar to their models, a sudden dambreak scenario is envisaged rather than a slow evolution of an ice-channel or erosion of bedrock constraining the ice-dam. The numerical results were developed for the most likely scenario where both the Kuray and Chuja basins were inundated to form one lake at a maximum water level of 2100 m asl (Carling et al 2010(Carling et al , 2011. The initial simulation assumes instantaneous removal of the ice barrier, which would have cut down significantly in as little as 11 h (Carling et al 2010), and this assumption is revisited in the Discussion section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to their models, a sudden dambreak scenario is envisaged rather than a slow evolution of an ice-channel or erosion of bedrock constraining the ice-dam. The numerical results were developed for the most likely scenario where both the Kuray and Chuja basins were inundated to form one lake at a maximum water level of 2100 m asl (Carling et al 2010(Carling et al , 2011. The initial simulation assumes instantaneous removal of the ice barrier, which would have cut down significantly in as little as 11 h (Carling et al 2010), and this assumption is revisited in the Discussion section.…”
Section: Methodsmentioning
confidence: 99%
“…The result was an ice-impounded meltwater-fed lake, which was the source for repeated catastrophic peak discharges of the order of 10 7 m 3 s −1 (Baker et al 1993;Herget 2005;Carling et al 2010). At maximum stand, which occurred within the later glacial stage (40-13 ka BP), Lake Kuray-Chuja had a volume of at least 594 km 3 and was 600-700 m deep at the deepest points, with a total surface area of 2951 km 2 (Carling et al 2011). Stratigraphic evidence in the main flood valley downstream of the ice-dam indicates that at least three large floods have occurred, with the largest one responsible for high-level flood bars deposited in side valleys and valley-wall alcoves.…”
Section: Regional Contextmentioning
confidence: 99%
“…1), as well as along the valleys of the Chuja and Katun rivers, which lead northward to the Ob river and thence to the Siberian plains (Carling 1996a;Carling et al 2002). The conjoined basins were occupied by a temporal series of ice-dammed lakes during the late Pleistocene (Marine Isotope Stages 2 and 3; Carling et al 2011) and dunes in the basins were formed when alluvial fan gravels, inundated by the lake, were mobilized as the lake emptied rapidly following the repeated failures of the ice-impoundment (Carling 1996b). Other gravel dunes were formed in the sediments deposited by the megafloods along the valleys below the former ice-dam (Carling 1996a;Huggenberger et al 1998), but these latter dunes are not considered here.…”
mentioning
confidence: 99%
“…The Chagan-Uzun glacier(s) reached farther downstream than mapped by Gribenski et al (2016), who did not recognize an extensive moraine reported earlier (Agatova, 2005;Bohorquez et al, 2015;Carling et al, 2011). This moraine was overlooked in some other studies (Butvilovsky, 1993;Lehmkuhl et al, 2004;Okishev, 2011) as it was significantly eroded during the emptying of Pleistocene ice-dammed lakes (e.g.…”
Section: Extent Of the Chagan-uzun Glaciersmentioning
confidence: 92%
“…The lower shoreline features show that the ice dam must have been in place after the Chagan-Uzun moraines were created (Carling et al, 2011;Bohorquez et al, 2015;Gribenski et al, 2016). It, or a precursor dam, must also have been existed before they were created, since the 2100 m shoreline is not represented on them.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%